Vulnerability to Natural Disasters and Insurance: Insights from the Italian Case - Francesco De Masi; Donatella Porrini (International Journal of Financial Studies, 2018)
The aim of this article is to analyze the concept of “vulnerability” to natural disasters, focusing on the specific case of the Italian earthquake insurance. In this sense, we examine in detail the vulnerability definition and its relevance for citizens and for insurance companies. Then we investigate the Italian insurance market characterized by a very low penetration of natural disasters insurance and the potential effects of a recent Government initiative called “Sisma Bonus”. The idea is that its technical content, in terms of a specific definition of vulnerability, may contribute to developing a better consciousness about vulnerability and a larger diffusion of insurance products.